Rare case of giant retroperitoneal sarcoma - Ghatnekar, Aditya; Nichkaode, Prabhat; Athavale, V. S.; Tonape, Trupti; Patil, Kuldip; Srilikhitha, K.; Ranka, Miten; Balasubramanyam, Sreekumar; Gogineni, Jyotsna (International Surgery Journal, 2019)
Schwannomas are benign nerve sheath tumors. Malignant schwannomas have been reported in literature but they frequently originate from the conversion of plexiform neurofibromatosis rather from the malignant degeneration of a benign schwannoma. Large retroperitoneal schwannomas are extremely rare tumours. They usually reach a large size when they arise retroperitoneally, which might raise suspicion for malignancy. Such tumors predominate in women schwannomas are usually solitary, slow growing and non- aggressive neoplasm usually found in head and neck region. Retroperitoneal schwannomas are usually large size are rare and are difficult to diagnose clinically. Nevertheless, the mainstay of management remains surgical removal and alternatively, the radio-therapy may prove to be effective. This case report of a 55 yrs male is based on such a patient in whom the diagnosis was established with great difficulty and intraoperative findings were something we had never encountered before.